Spatial Variability of Total Nitrogen, pH, and Organic Carbon in Organic and Inorganic Farming - Yagus Wijayanto; Anggara Dwi Pamungkas (Universitas Muhammadiyah Surakarta, 2022)
Efforts have been made to transform traditional farming practices to organic method in order to ensure sustainable production and environmental conservation. Studying the differences between these two practices through mapping provide insight into the effectiveness of the transformation, as soil characteristics varies in space. Therefore, this study examined the spatial variability of Total Nitrogen, pH, and Organic Carbon in Lombok Kulon village, Wonosari Sub-district, Bondowoso district. The method used consists of: (a) data collection; (b) data input in GIS; (c) processing data, (d) analysis and (e) presentation of results. The results showed that soil organic content in the area was generally low. Furthermore, indicators such as pH, Organic Carbon and Total Nitrogen do not present significant differences between organic and Inorganic practices. The use of Kriging in GIS environment to analyze spatial variability showed variations and inform management decisions relevant to Total Nitrogen, pH and Organic Carbon.